Francisco Zúñiga Díaz, a man-at-letters - Castro-Carvajal, Hiram (2023)
In this article, the author describes the importance of Costa Rican writer Francisco Zúñiga Díaz, leader and responsible of the well-known literary workshop founded at the National Institute of Insurances (INS) in 1979 to bring together INS’s employees interested in poetry and short story